(untitled) (KULT_online, 2020)
The editors of the The Routledge Research Companion to Travel Writing, Alasdair Pettinger and Tim Youngs, are leading experts in the field of travel writing. Their newest volume brings together contributions that examine key themes in travel writing, scrutinize novel and established approaches to the genre, and map new paths in the field of travel writing studies. Each individual contribution is persuasively argued and demonstrates its arguments and findings with examples of representative primary texts. The diversity of the travel narratives analyzed in the volume exemplifies the heterogeneity and richness of the genre. This makes for a compelling read for those who are new to the field as well as for those who are acquainted with the study of travel writing.